MENTAL ACCOUNTING: THE MEANING OF ‘BUWUHAN’ IN JAVANESE WEDDING TRADITION: AN ETHNOGRAPHIC STUDY - Abdul Manan, Abdul Manan; Rusdiana Permanasari, Rusdiana Permanasari; Nanang Ari Utomo, Nanang Ari Utomo; Sujito, Sujito (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
The tradition of buwuhan, or donation, is integral to Javanese traditional wedding ceremonies. This practice not only functions as financial support but also reflects social values such as collectivism and reciprocity within the community. This study aims at identifying the mental accounting practices involved in the buwuhan tradition during Javanese weddings and to analyse the symbolic meaning of financial management related to buwuhan. The research adopted a qualitative approach using an ethnographic method, with data collected through direct observation, interviews, and analysis of relevant documents. The informants included traditional elders, community leaders, and individuals who had participated in the wedding procession. The main finding revealed that the practice of buwuhan is perceived as a form of kepotangan a social debt or reciprocal obligation. As a result, many households manage their budgets by prioritising the fulfilment of these obligations over other financial needs.